2016
DOI: 10.1163/1568539x-00003322
|View full text |Cite
|
Sign up to set email alerts
|

Effect of substrate temperature on behavioural plasticity in antlion larvae

Abstract: Temperature is of crucial importance, affecting all aspects of insect life such as survival, development and daily activity patterns, and consequently behaviour. In the present study we evaluated the effect of temperature on the behavioural plasticity of antlion larvae, the sit-and-wait predators, which are considerably more dependent on local habitat conditions. We provided ethological descriptions of pit construction and feeding behaviour. An increase in temperature led to greater activity and consequently t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 43 publications
2
10
0
Order By: Relevance
“…The results of our experiment show that higher soil temperatures resulted in more frequent trap building and traps with a larger diameter and volume. These findings are consistent with those from some earlier studies on trap building in antlion larvae (Kitching 1984 ; Arnett and Gotelli 2001 ; Klokočovnik et al 2016 ), but they contrast with the conclusions of other studies showing either no clear effects of temperature on trap volume (Rotkopf et al 2012 ) or negative effects of temperature on trap-building frequency (Klein 1982 ). Our findings do not support hypothesis 2, which predicts that antlion larvae challenged by cooler conditions might compensate for their reduced behavioral capacity to immobilize prey and prevent rescue by ant nest-mates by maintaining larger traps.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The results of our experiment show that higher soil temperatures resulted in more frequent trap building and traps with a larger diameter and volume. These findings are consistent with those from some earlier studies on trap building in antlion larvae (Kitching 1984 ; Arnett and Gotelli 2001 ; Klokočovnik et al 2016 ), but they contrast with the conclusions of other studies showing either no clear effects of temperature on trap volume (Rotkopf et al 2012 ) or negative effects of temperature on trap-building frequency (Klein 1982 ). Our findings do not support hypothesis 2, which predicts that antlion larvae challenged by cooler conditions might compensate for their reduced behavioral capacity to immobilize prey and prevent rescue by ant nest-mates by maintaining larger traps.…”
Section: Discussionsupporting
confidence: 91%
“…Given that the capacity to build traps can directly reflect the dependence of larval behavior and metabolism on temperature, we expected soil temperature to positively affect pitfall trap volume (hypothesis 1). Such an effect was previously found in Myrmeleon pictifrons (Kitching 1984 ), Myrmeleon immaculatus (Arnett and Gotelli 2001 ) and E. nostras (Klokočovnik et al 2016 ). However, other studies showed contrasting effects of temperature on trap building.…”
Section: Introductionsupporting
confidence: 66%
See 2 more Smart Citations
“…The activity of antlion larvae is highly temperature‐dependent (Klein, ; Marsh, ; Ábrahám, ; Scharf & Ovadia, ; Klokočovnik et al, ; Antoł et al, ); therefore, antlions migrate deep into the sand at high sand‐surface temperatures (Heinrich & Heinrich, ; Matsura, ; Van Zyl et al, ). Antlions are extremely sensitive to substrate vibrations produced by prey moving on the sand surface (Devetak et al, ; Fertin & Casas, ; Devetak, ; Martinez et al, ); therefore, we anticipate that vibrational cues would stimulate them to move to the surface when buried in deeper layers of sand.…”
Section: Introductionmentioning
confidence: 99%